THE IMPACT OF CHANGES IN THE VALUE OF HARM ON JUDICIAL COMPENSATION A COMPARATIVE STUDY BETWEEN THE LAWS OF EGYPT AND OF THE UNITED ARAB EMIRATES - Dr. Abd El Hakam El Khon (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
It is well known that the judge, in determining the compensation should consider the scope of the harm at the time of issuing his court ruling Consequently he should take into consideration any changes that may have occurred to the harm from the time it has actually occurred until the time he issues his ruling. The scope of the harm in many cases changes by time either increasing or decreasing due to foreseen or unforeseen developments. This is particularly true in cases of physical harm which is greatly affected by any developments which may lead to its continuation or amelioration or aggravation The harm inflicted on the injured may change not in its scope , nor itself nor its components but in its value where the harm remains constant and so do its components but its value changes as a result of economic or financial circumstances that may affect the purchasing power of money, in which case the change of the harm would be due to external causes that are not relevant neither to the harm itself nor to the nature of its components. This raises the question of the impact of change in the value of the harm on the compensation due to the harmed person. The answer to this question differs according to whether the change in the harm has occurred before or after the issuing of the final court ruling.